Efektivitas Zona Selamat Sekolah di Jalan Taman Siswa, Sekaran, Kecamatan Gunungpati, Kota Semarang - Sholahudin, Farhan Sholahudin; Bambang Haryadi; Sigit Arya Panuntun; Alia Safira, Reishya; Aviv Setiawan; Rohadatu Resty Auzia (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2024)
The installation of School Safe Zones on Taman Siswa Street is considered suboptimal, given that many road users still travel at high speeds and pedestrians, especially students, teachers, and the surrounding community, have not utilized the School Safe Zones facilities. The purpose of this study is to determine the effectiveness of School Safe Zones on Taman Siswa Street, particularly in the school areas of SD N Sekaran 1, SD N Sekaran 2, and MI Roudlotul Huda. The urgency of this research is to evaluate the installation of School Safe Zones on Taman Siswa Street, especially in the school areas of SD N Sekaran 1, SD N Sekaran 2, and MI Roudlotul Huda. The approach taken includes surveys of vehicle speed, pedestrian behavior, drop-off behavior, and road equipment facilities. The results of this study are expected to benefit road users, particularly pedestrians in the school areas, by enhancing safety and security when walking and crossing the street. Based on the analysis results, it can be concluded that the effectiveness at School Safe Zones locations is still inadequate, as many students are crossing improperly, and the behavior of escorts is also not ideal. Additionally, road users are still driving at high speeds despite the presence of School Safe Zones signage.